Radial head replacement (literature review) - Boyko, Igor; Shcherbakov, Dmitriy; Makarov, Vasyl; Lazarenko, Gleb (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
On the basis of the literature analysis, various variants of the radial head endoprostheses, which were used earlier and are now used in clinical practice, are considered: monobloc, individual monobloc, sectional modular monobloc, bipolar modular. The generally accepted classification of endoprostheses does not exist for the radial head — today they are distributed by design to monoblocal and bipolar. Monoblocal endoprosthesis can be either modular or sectional. Bipolar radial head endoprosthesis has joint between the implant head and the leg of the hinge node, an additional degree of freedom in which provides the maximum congruent location of the head of the endoprosthesis during flexsion, extension and rotation of the radius in the elbow joint. The biomechanical peculiarities of the functioning of different types of endoprostheses are determined, sort-term and long-term clinical results of their application are shown. The indications for radial head replacement are: the lack of technical ability to perform internal fixation of Mason-Hotchkiss types III and IV injuries, as well as in the case of additional destabilizing disorders of the capsule-ligamentous apparatus, Essex-Loprest type injury, and instability of the elbow and/or pain in the arm after radial head resection, its unsatisfactory osteosynthesis, tumors of the proximal radius. The authors claim that in case of use of metallic endoprostheses, the radial head restores the valgus stability of the elbow to the normal level. From the first radial head replacement has passed over than 75 years, and the search for an ideal endoprosthesis is relevant. Despite the large number of designs and types of endoprosthesis, there is currently no implant that works as a natural radial head. All technological improvements are aimed at increasing the life of implants and minimizing injuries to the cartilage and soft tissues both during installation and in the process of work.